Portuguese juvenile delinquents: An exploratory study from a sample of institutionalized young offenders - Morgado, Alice Murteira (2017)
Severe antisocial behaviour in adolescence is a matter of concern in every society, especially when it translates in juvenile delinquency that persists through adulthood. In this study, we asked a sample of 121 institutionalized male juvenile offenders (between 14 and 20 years old) to fill several self-report measures to understand young delinquents and their social and academic conditions, behaviour, and individual dispositions. Results reveal peculiarities on academic achievement, socioeconomic status and family size. Analysis confirmed the role of personality, self-concept, self-control and family environment on antisocial scores, especially psychoticism, neuroticism, social conformity, and family environment. Different behavioural subtypes reflect differences in psychoticism, antisocial behaviour and family environment. However, there were no correlations between antisocial tendency and age, school year or family size. Our paper contributes to existing knowledge that supports intervention approaches, stressing that, unlike age, school year or family size, different types of behaviour may require differentiated interventions.